The vibrational spectrum of Nd2BaZnO5 - Baran, Enrique José (1994)
In a previous paper we presented a general analysis of the infrared spectra of the different Ln2BaMIIO5 structural types [2]. As the tetragonal I4/mcm structure is only present in La2BaZnO5 and Nd2BaZnO5 we have now attempted to obtain a deeper insight into its vibrational behaviour by careful analysis of the Raman and infrared spectra of Nd2BaZnOs, for which a detailed structural analysis has been published recently.